CURRENT APPLICATIONS OF GENE TECHNOLOGY TO MEDICINE AND AGRICULTURE IN SELECTED EUROPEAN COUNTRIES (UK, FRANCE, GERMANY - Thu Hien, Le Thi; Thu Ha, Le Thi; Bich Hang, Pham Le; Ha, Nguyen Hai (Vietnam Journal of Biotechnology, 2018)
In European countries, particularly in the United Kingdom, France, and Germany, grants for biotechnology, especially in gene technology, are growing rapidly each year, and boosting the development of industries. In the field of medicine and health care, these countries focus on the diagnosis of genetic diseases, cancers, transmission diseases by polymerase chain reaction - related techniques, and next generation sequencing technologies (NGS); implementing clinical trials for the treatment of cancers and single-gene genetics by gene therapy; improving the prevention by using recombinant vaccines. Advanced genetic engineering shortens diagnostic time and improves accuracy compared to conventional diagnostic methods and offers new hope to patients with serious diseases, limiting the spread of communicable diseases, thereby improving the quality of health care in the future. In the area of agriculture, the typical application of modern biotechnology is the development of genetically modified organisms including plants and animals with desired characteristics. In these countries, however, the cultivation of genetically modified plants or the importation of genetically modified food and feed is restricted by strict government regulations on biosafety. But overall, in comparison with other countries in the region and in the world, the United Kingdom, France, and Germany have advanced genetic engineering with a number of  research projects that benefit people in various fields, improving the quality of life.